Inverse pole figure of CVD coatings of metal cutting tools using an XRD Bragg Brentano geometry. Issue 2 (June 2022) - Shibata, Tomohiro
Abstract : CVD-coated cemented carbides are widely used for various metal cutting applications. It has been established that the textures of the coating materials especially that of the α -Al2 O3 greatly affect the cut performance for some applications. The characterization of the coating texture is thus very important. In this paper, inverse pole figures of α -Al2 O3 based on XRD with Bragg Brentano geometry were calculated for several metal cutting inserts available in the market. This method is simple, less time-consuming and can be applied to previously collected data and is compared with that of the EBSD. Despite several differences, IPF maps based on XRD powder diffraction represent the texture of metal cutting inserts.